Understanding the Economics of Solar Powered Irrigation System in Bangladesh - Akter, Taslima; Bari, Kazi Ehsanul (Future Science / FSH-PH Publications, 2022)
Solar pump is a more environmental-friendly irrigation option for farmers in Bangladesh. Researchers have found that using solar pump for irrigation is more cost effective. Researchers have found that using solar pump for irrigation is more cost effective as well as less damaging for the environment. Moreover, this relies on renewable energy sources that make it more efficient. Against this backdrop, the objectives of the present study were to understand the profitability analysis of using solar pumps instead of the diesel-run pumps for irrigation and also to identify its determinants. The study collected primary data from four upazilas of Jhenaidah district, purposively selected as the study site. Data were collected from the respondents whose families are involved in agricultural activities. For the analysis of collected data, the study used cost-benefit analysis, while a logit regression analysis was also done for understanding the determinants of using solar energy for irrigation. It is found that the benefit-cost ratio for using solar pump for irrigation by the farmers is 0.277, which implies that the cost is more than the benefit if the households adopt solar pump instead of diesel pumps. On the other hand, the Logit regression analysis found that bigger household size, nearby water sources for irrigation, perceptions on improved production and higher current year yield significantly influence the usage of solar pumps for irrigation. On the contrary, if households were entitled to share irrigation facilities, they are less likely to use solar pumps for irrigation.